Residents' Satisfaction On Low Cost Housing In Penang - Yeoh, Mooi Mooi (Universiti Sains Malaysia, 2004)
Satisfaction with housing is one of the key factor contribute to the overall satisfaction with the quality of life and unsatisfaction with the dwelling unit will create a negative impact to the development of the residents. The purpose of this research was to evaluate the resident's level of satisfaction on low cost housing in Penang. The sample size of 220 respondents was chosen to represent the overall residents residing in the low cost housing in Penang.